Ontogenetic development and redescription of Tribolonychus collyerae (Acari: Tetranychidae) - Yi, Tian-Ci; Fan, Qing-Hai; Zhang, Zhi-Qiang (Zootaxa, 2013)
Tribolonychus collyerae Zhang & Martin is redescribed based on the larva, protonymph, deutonymph and adult male and female specimens from New Zealand. The ontogenetic development of chaetotaxy in Tribolonychus and the number and position of solenidia on tibia I are discussed. Patterns of setal addition on leg III and IV from larva to adult in Trilobonychus are different from the basic pattern of the Tetranychinae and allied genus Neonidulus.